Review Zerbino DD, Bagriy MM, Diadyk OO [et al]. [Vascular renal pathology]. Vinnitsa: New book; 2015. 456 p. Ukrainian. - Editorial office of journal "Morphologia" (Морфологія, 2016)
The monograph presents all the major pathological processes and diseases that develop in the blood vessels of the kidneys.